Full-pattern analysis of time-of-flight neutron transmission of mosaic crystals - Malamud, Florencia (2016)
The energy-resolved neutron transmission of mosaic crystals contains a series of dips in intensity, at specific neutron wavelengths defined by the orientation of the specimen in the neutron beam. This article presents a Rietveld type full-pattern analysis of neutron transmission experiments on mosaic crystals performed at spallation pulsed neutron sources. The proposed analysis provides precise and simple determination of lattice parameters, mosaicity, extinction factors and crystal orientation, and is especially suited to investigate the spatial variation of such microstructural information across macroscopic specimens with ∼1 mm resolution. The effect of extinction on the intensity of Bragg reflections has been successfully accounted for by a parameter measuring the ratio of the beam attenuation due to Bragg reflection to the combined attenuation due to absorption and scattering processes. Experiments were performed at the ENGIN-X beamline, ISIS Facility, UK, on several naturally occurring and man-made mosaic crystals, including a copper monochromator at temperatures between 55 and 300 K, an iron-nickel meteorite, and a natural pyrite crystal. Typical experimental resolutions found for lattice parameters and mosaicity are 0.03 and 7%, respectively. The possibilities of the technique for quantitative phase and/or texture analysis of specimens composed of several grains or phases are discussed.